KAJIAN VISUAL TERHADAP BUKU PANDUAN UNTUK ANAK-ANAK PADA MUSEUM NASIONAL INDONESIA YANG BERJUDUL ‘AYO KE MUSEUM NASIONAL INDONESIA!’ - Henny Hidajat (Universitas Bunda Mulia, 2020)
Visiting museums is a method to upgrade knowledge and appreciation to national cultural heritage, beside recreation activity. This method is also often applied by educational institution and families as one of their edutainment activity. Museum Nasional Indonesia as the central museum, with various collection, exhibits the timeline of Indonesian cultural heritage since Prehistoric period to the coming of Western colonials in their permanent exhibition, which have been visited mostly by children, with their families or with their school. Therefore, the museum management shared some information media to enable the children to comprehend the collections and other explanations displayed in the museum. One of the information media is guidebook for children titled “Ayo ke Museum Nasional Indonesia!”,which shared to the visitors, mostly children in groups. However, the book can be evaluated both information content and the visual appearance, to optimize the function and artistic approach. The article is based on research that aimed to study and evaluate museum guide book for children “Ayo ke Museum Nasional Indonesia!” that published by Museum Nasional Indonesia, focusing on the information content and visual appearance, through observation to the book and the series using children education and visual theories, that will produce a recommendation to optimized the guide book and hopefully may enable children to comprehend the collections and the storyline in a cheerful way, therefore they may appreciate the history and the heritage, and to encourage them to revisit the museum.